Efek Efek Kausal Pada Aturan Permohonan Dispensasi Kawin - Prasasti Dyah Nugraheni (Istinbath : Jurnal Hukum, 2020)
This paper contains legal issues arising from the promulgation of the Supreme Court Regulation Number 5 of the Year, which is a legal substance derived from Law Number 16 of 2019. The research method used in this paper is normative legal research which is carried out using secondary data. or library data. Das sollen, as an implication of the new regulation, creates a potential that makes applications for dispensation of marriage wide open. This is evidenced by the existence of a court decision, one of which is Decision Number: 13 / Pdt.P / 2020 / PA.Bgi., Which makes giving dispensation to marriage for those who are not yet old enough, on the basis of consideration of fulfilling administrative requirements, which are in accordance with the provisions of Article 7 paragraphs (1) and (2) of the Marriage Law jo. Article 6 (e) Government Regulation Number 9 of 1975. Therefore, it is very necessary to make new statutory provisions, which are limitative in nature, so that, it is hoped, can minimize deviant practices of the provisions regarding the marriage age limit for women and men who want to get married but not old enough.